1995
DOI: 10.1002/mrm.1910340609
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of liver blood volume: comparison of ultra short ti inversion recovery echo planar imaging (ulstir‐epi), with dynamic 3d‐gradient recalled echo imaging

Abstract: An ultra-short TI inversion recovery echo-planar imaging (ULSTIR-EPI) sequence was designed to reduce the influence of water exchange on fractional tissue blood volume (BV) estimation by measurement of T1-changes induced by a gadolinium-based macromolecular contrast medium (MMCM). Fractional liver BV in rats, estimated by ULSTIR-EPI was compared for accuracy to a fast T1-weighted three-dimensional gradient-echo (3D-SPGR, 3D-spoiled gradient recalled acquisition in a steady state) sequence using an in vitro ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…[4]) and also the slow-exchange regime with b ϭ 1 3 s (two-site model) for different combinations of TI and E. This was carried out twice, either with F set to 100 or 500 ml/100 g/min. The high value of F was chosen in order to illustrate the situation in the heart during maximal perfusion, such as after administration of dipyridamole.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4]) and also the slow-exchange regime with b ϭ 1 3 s (two-site model) for different combinations of TI and E. This was carried out twice, either with F set to 100 or 500 ml/100 g/min. The high value of F was chosen in order to illustrate the situation in the heart during maximal perfusion, such as after administration of dipyridamole.…”
Section: Simulationmentioning
confidence: 99%
“…Several studies have indicated that this could affect the results of such perfusion measurements (1)(2)(3)(4)(5)(6). However, contrast-enhanced MRI using T 1 -weighted imaging has been developed in order to measure perfusion or perfusion-related parameters of the heart in vivo without explicitly considering the effect of water exchange.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver blood volume has been quantified with MRI and macromolecular agents (14,15). More recently, hepatic perfusion has been assessed by pharmacokinetic analysis of dynamic MR images obtained after bolus injection of a commercially available extravascular agent (16).…”
mentioning
confidence: 99%
“…Since most living tissues do not exhibit such extreme exchange characteristics (6,(12)(13)(14), neither of these assumptions accurately describes the biological system. However, it was predicted that the sources of error due to physiologic variations can be minimized by carefully selecting pulse sequence and calculation methods (5).…”
mentioning
confidence: 99%